Achieving biodiesel standards through saturation level optimisation - Masera, Kemal; Hossain, Abul Kalam; Griffiths, Gareth (Frontiers in Fuels, 2025)
Biodiesels made from waste feedstock are viable sustainable fuels for compression-ignition engine use. However, biodiesels produced from single waste sources do not always comply with the European biodiesel standard. This study investigates fuel quality and engine performance when two biodiesels with different characteristics are blended at various proportions. Waste cooking oil biodiesel was blended with sheep fat biodiesel, which has a lower unsaturated fatty acid content. The engine performance, combustion, and exhaust emission characteristics of the neat biodiesels and their blends (at 60/40, 50/50, and 30/70 ratios) were analysed. The results showed that 60/40 and 50/50 blends met the core parameters of the BS EN 14214 biodiesel standard and improved combustion and emission characteristics compared to neat biodiesels and diesel. The 50/50 blends gave up to 5% and 14% improvements in the in-cylinder pressure and maximum heat release rate, respectively, compared to the same results for neat biodiesel operation. Reduction of up to 73% in CO, 96% in smoke and 3% in CO2 emissions was observed. However, NOx emission was 2.5% higher than diesel. The results reveal that carefully selected biodiesel–biodiesel blending could meet fuel standards, improve engine performance, and reduce exhaust emissions.